Eksplorasi Aspek Bioekologi dan Status Konservasi Ikan Endemik Sumatera Rasbora spilotaenia Hubbs & Brittan, 1954 - Rambe, Kumpulan; Harahap, Muhammad Ali Badrun; Pratiwi, Andira; Gultom, Yenni Amelia; Sagala, Fiqri Adam; Khairul, Khairul (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Rasbora spilotaenia is one of the endemic fishes of Sumatra Island. Its natural habitat is found in Aek Kanan and is included in the administrative area of North Padang Lawas Regency. Until now there has been no data and information related to the bioecological aspects of R. spilotaenia reported from the North Padang Lawas Regency area. The aim of the study was to determine the bioecological aspects of R. spilotaenia and its conservation status in IUCN. The research conducted was exploratory with the determination of the observation station point by purposive sampling. Fish were caught using 2 different mesh sizes, namely sizes, ⅟₂ and ¼ inch. Samples of fish caught were measured in total length and weight, and the number of males and females were counted. Data were analysed using descriptive statistics. Based on the frequency distribution data, the most length class was found to be 6.5-7.8 cm (8 individuals) and the least was 5.1 -6.4 cm (0), the sex ratio between males and females (1:2), the highest population density at Station 2 (0. 91 individuals/100 m2) and lowest at Station 1 (0.06 individuals/100 m2), length-weight relationship with R2 value (0.9562), and parameters of mean temperature (27oC), brightness (111.33 cm), depth (1.01 m), current (0.46 m/s), pH (5.67), and DO (6.6 mg/L). It was concluded that the bioecological aspects of R. spilotaenia in Aek Kanan are still stable towards population conditions and natural habitats still support the life of fish, but for conservation status needs a little attention.